Comparatives Study of Production Biodiesel from Soybean oil and Jatropha Curcas Seeds Oil - Uthman, Habibu; A. Saka, Abdulkareem (Distributed Generation & Alternative Energy Journal, 2013)
This study involves transesterification of soybean and Jatropha oils with methanol, using sodium hydroxide as the catalyst to produced biodiesel as an alternative to petroleum diesel. This work investigates the effects of temperature and time on the production of biodiesel from the feed stocks employed. Also investigated are the effects of particle size and temperature on the production of oil from the Jatropha seed. The produced biodiesels from soybean and Jatropha oil were character- ised to determine their suitability as a replacement for the petrol diesel. Results obtained shows that both temperature and time influence the production of biodiesel from the soybean and Jatropha oil. Analyses of the produced biodiesels also indicates that the properties of the biodie- sels produced shows that the density, refractive index, moisture content, viscosity, flash point, cetane number, pour point and sulphur content of the biodiesel produced from soybean oil are 0.882g/cm3, 1.486, 0.018%, 6.24cP, 148°C, 51.3, –8.2 and 0.004% respectively. While the correspond- ing values of these properties for the biodiesel produced from Jatropha oil are 0.861g/cm3, 1.532, 0.013%, 2.8cP, 89°C, 49.5, –7.9 and 0.001%. It can be inferred from the results on the properties of biodiesel that the properties of the produced biodiesels from soybean and Jatropha oils fit well within the set limits for the standard biodiesel and fossil diesel, the biodiesel can therefore be used as a replacement for the petrol diesel. Results of various analyses conducted on the biodiesels produced from soybean and Jatropha oil shows that biodiesel of good qualities can also be produced from the Jatropha oil and can be used as a substitute for production of biodiesel from soybean which is edible oil.